Răspuns :
m×1^2 + 1 - 3 = 0
m-2=0
m=2
2x^2 + x - 3 = 0
delta = 1 - 4×2×(-3)
delta = 1 + 24 = 25 =>rad.delta = 5
x1=(-1-5)/(2×2)=-6/4=-3/2
x2=(-1+5)/(2×2)=4/4=1
m-2=0
m=2
2x^2 + x - 3 = 0
delta = 1 - 4×2×(-3)
delta = 1 + 24 = 25 =>rad.delta = 5
x1=(-1-5)/(2×2)=-6/4=-3/2
x2=(-1+5)/(2×2)=4/4=1
daca x = 1 inseamna ca m*1² + 1 - 3 = 0
m = 3 - 1
m = 2
Proba: 2x² + x - 3 = 0 => Δ = 1² - 4*2*(-3) = 1 + 24 = 25
[tex]\sqrt\Delta=\pm5[/tex]
[tex]x_{1;2}=\frac{-1\pm5}{4}=\;\boxed{x_1=1}\;\;si\;\;x_2=-6/4=-3/2[/tex]
m = 3 - 1
m = 2
Proba: 2x² + x - 3 = 0 => Δ = 1² - 4*2*(-3) = 1 + 24 = 25
[tex]\sqrt\Delta=\pm5[/tex]
[tex]x_{1;2}=\frac{-1\pm5}{4}=\;\boxed{x_1=1}\;\;si\;\;x_2=-6/4=-3/2[/tex]